ABO blood grouping: A potential risk factor for early childhood caries - A cross-sectional study - Lavanya Govindaraju; Ganesh Jeevanandan; E M G Subramanian (Wolters Kluwer Medknow Publications, 2018)
Aim: The paradigm of etiology of early childhood caries (ECC) is shifting toward genetics. Of various inherited factors, blood group of an individual is genetically determined. The aim of the study is to determine if blood group of an individual will serve as a potential risk factor in the development of ECC. Materials and Methods: A cross-sectional study was conducted in Chennai. Blood samples were collected from a total of 500 children <71 months of age for determination of the blood group. Of which 96 children (24 per blood group) were randomly selected and were included in the study. Oral screening of the selected children was done by a pediatric dentist who was blinded to the blood group of the children. Decayed, extracted, and filling index was noted. Details on other associated factors for the development of ECC such as the socioeconomic status, oral hygiene measures, diet, and feeding practices were collected by directly interviewing the parents through a questionnaire. Statistical analysis was done using Chi-square and Kruskal-Wallis test and post hoc Tukey test with significance level set at 0.05. Results: Intergroup analysis of the associated factors showed no significant differences between the children of different blood groups. A statistically significant relation was noted between the blood groups and development of ECC (P = 0.025). Conclusion: Blood group is a potential risk indicator for the development of ECC.